LEGAL REGULATION OF RELATIONS BETWEEN THE STATE AND RELIGIOUS ORGANIZATIONS IN UKRAINE AND COUNTRIES OF THE EUROPEAN UNION - Chervenkova, Marina G. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: to study the current legal regulation of relations between the state and religious organizations in Ukraine and the European Union countries in order to determine the optimal model and mechanisms for their regulation. A system of sectoral legislation and norms of European law are considered. Methods: empirical, optimization and comparison. Results: an analysis of the legal regulation of relations between the state and religious organizations in the field of education in the process of European integration and reform of the legislation is carried out. The experience of European countries in the regulation of educational religious relations is researched. Discussion: national and international regulations relating to relations between the state and religious organizations.